solution of transcedental equation

2 views (last 30 days)
shiv gaur
shiv gaur on 14 Oct 2021
Commented: Matt J on 14 Oct 2021
function beta1 = trial0(beta, eps1, eps2, epsm,k0,h)
S1 = sqrt(power(beta,2)-(eps1*power(k0,2)));
S2 = sqrt(power(beta,2)-(epsm*power(k0,2)));
S3 = sqrt(power(beta,2)-(eps2*power(k0,2)));
beta1 = tanh(S2*h)*((eps1*eps2*power(S2,2))+(power(epsm,2)*S1*S3)) + (S2*((eps1*S3)+(eps2*S1))*epsm);
end
eps1 = 1.5471;
eps2 = 1.5431;
eps1m = -9.894 ;
epsm2 = 1.0458;
epsm = eps1m + i*eps2m;
lambda = 633;
k0 = (2*pi)/lambda;
h = 50;
find the value of beta
  1 Comment
Catalytic
Catalytic on 14 Oct 2021
You have not accepted any answers previously provided to you. That is a bit of a disincentive for people to help you.

Sign in to comment.

Answers (1)

Matt J
Matt J on 14 Oct 2021
Edited: Matt J on 14 Oct 2021
eps1 = 1.5471;
eps2 = 1.5431;
eps1m = -9.894 ;
eps2m = 1.0458;
epsm = eps1m + i*eps2m;
lambda = 633;
k0 = (2*pi)/lambda;
h = 50;
[b,fval]=fminsearch(@(b) abs(trial0(complex(b(1),b(2)), eps1, eps2, epsm,k0,h)) ,[1,1]);
beta=complex(b(1),b(2)), fval
beta = -0.0145 - 0.0004i
fval = 2.7735e-05
function beta1 = trial0(beta, eps1, eps2, epsm,k0,h)
S1 = sqrt(power(beta,2)-(eps1*power(k0,2)));
S2 = sqrt(power(beta,2)-(epsm*power(k0,2)));
S3 = sqrt(power(beta,2)-(eps2*power(k0,2)));
beta1 = tanh(S2*h)*((eps1*eps2*power(S2,2))+(power(epsm,2)*S1*S3)) + (S2*((eps1*S3)+(eps2*S1))*epsm);
end
  7 Comments
Matt J
Matt J on 14 Oct 2021
Well, if we've answered your first question, please Accept-click it and post the related question in its own thread.

Sign in to comment.

Products


Release

R2021a

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!